Queer in Queen: Camp Aesthetics and Queer Performativity in Queen’s Music Videos - Botescu Sireteanu, Ileana (Transilvania University of Brasov, 2019)
The present paper situates its concerns at the crossroads of cultural studies, queer studies and visual culture in an effort to illustrate how queer identity is visually performed and formed through a particular aesthetic discourse that foregrounds kitsch, excess and self-conscious parody. Consecrated by Susan Sontag in 1964 as camp aesthetics, this visual discourse generates artistic acts whose major goal is to reach beyond ideological categories, hierarchies, dichotomies in order to destabilize their authority. This study focuses on some of Queen’s music videos in an attempt to argue that they represent clear instances of camp visuality designed by the band’s front man, Freddie Mercury, as part of a therapeutic artistic form of coping with his own queerness. In this respect, the present paper explores the connections between these particular visual representations and their potential to destabilize traditional master narratives such as heteronormativity.
Keywords: visual culture; camp aesthetics; the politics of queerness; gender discourse; difference; stereotype